Exploration of factors which influence the involvement of specialist registered nurses in clinical teaching of advanced midwifery students in a tertiary hospital in Gauteng - Dr Du-Pleussis, MAR (University of Pretoria, 2022)
Dissertation (Med (Nursing ))--University of Pretoria, 2022.